Rural Poverty Alleviation in Brazil : Towards an Integrated Strategy, Volume 1. Policy Summary - World Bank (Washington, DC, 2013)
This report finalized in March 2001 constitutes a step toward the objective of designing an integrated strategy for rural poverty reduction in Brazil, The report contains an updated and more detailed profile of the rural poor in the northeast (NE) and southeast (SE) of Brazil; identifies key determinants of rural poverty in these regions; and proposes a five-pronged strategic framework in which to couch a set of integrated policies that could effectively help to reduce rural poverty in Brazil. This tentative set of policy options was identified via an analysis of rural poverty determinants complemented with an evaluation of relevant current public programs and six in-depth thematic studies that bear on critical components of the proposed integrated policy approach aimed at reducing rural poverty in the NE and SE of Brazil: 1) the dynamics of the Brazilian small farm sector, 2) rural labor markets, 3) rural land markets, 4) rural non-farm employment, 5) rural education, and 6) rural pensions. While this study emphasizes primarily microeconomic events--such as the impact of schooling, income transfers, and access to land and credit--poverty reduction requires both economic growth (macro-level) and specific anti-poverty policies (micro-level).